ΔNp63 knockdown mice: A mouse model for AEC syndrome - Maranke I. Koster (2018)
Dominant mutations in TP63 cause ankyloblepharon ectodermal dysplasia and clefting (AEC), an ectodermal dysplasia characterized by skin fragility. Since ΔNp63α is the predominantly expressed TP63 isoform in postnatal skin, we hypothesized that mutant ΔNp63α proteins are primarily responsible for skin fragility in AEC patients. We found that mutant ΔNp63α proteins expressed in AEC patients function as dominant-negative molecules, suggesting that the human AEC skin phenotype could be mimicked in mouse skin by downregulating ΔNp63α. Indeed, downregulating ΔNp63 expression in mouse epidermis caused severe skin erosions, which resembled lesions that develop in AEC patients. In both cases, lesions were characterized by suprabasal epidermal proliferation, delayed terminal differentiation, and basement membrane abnormalities. By failing to provide structural stability to the epidermis, these defects likely contribute to the observed skin fragility. The development of a mouse model for AEC will allow us to further unravel the genetic pathways that are normally regulated by ΔNp63 and that may be perturbed in AEC patients. Ultimately, these studies will not only contribute to our understanding of the molecular mechanisms that cause skin fragility in AEC patients, but may also result in the identification of targets for novel therapeutic approaches aimed at treating skin erosions. © 2009 Wiley-Liss, Inc.